2020
DOI: 10.1515/pjbr-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Sex care robots

Abstract: AbstractThe creation and deployment of sex robots are accelerating. Sex robots are service robots that perform actions contributing directly towards improvement in the satisfaction of the sexual needs of a user. In this paper, we explore the potential use of these robots for elder and disabled care purposes,which is currently underexplored. Indeed, although every human should be able to enjoy physical touch, intimacy, and sexual pleasure, persons with disabilities are often not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 58 publications
0
6
0
8
Order By: Relevance
“…Although we sampled sex doll owners in a broad sense, we did not target any particular subgroup based on the function or circumstances of their doll ownership. Previous qualitative work has reported many motivations for owning a sex doll, including sexual gratification, physical or emotional intimacy, and medical treatment (Eichenberg et al, 2019;Fosch-Villaronga & Poulsen, 2020;Langcaster-James & Bentley, 2018;Morgan, 2009;Valverde, 2012). It might be that those owning a doll specifically for sexual gratification (vs. emotional companionship or health reasons) have a different psychological profile, but our sample is not large enough to conduct such an analysis.…”
Section: Limitations and Future Directionsmentioning
confidence: 97%
“…Although we sampled sex doll owners in a broad sense, we did not target any particular subgroup based on the function or circumstances of their doll ownership. Previous qualitative work has reported many motivations for owning a sex doll, including sexual gratification, physical or emotional intimacy, and medical treatment (Eichenberg et al, 2019;Fosch-Villaronga & Poulsen, 2020;Langcaster-James & Bentley, 2018;Morgan, 2009;Valverde, 2012). It might be that those owning a doll specifically for sexual gratification (vs. emotional companionship or health reasons) have a different psychological profile, but our sample is not large enough to conduct such an analysis.…”
Section: Limitations and Future Directionsmentioning
confidence: 97%
“…The outcome may be financial or psychological, such as wellbeing. Research has shown that engaging with AI-powered robots may bring users pleasure (e.g., as a companion for older adults, sex robots) (Chen 2018 ; Fosch-Vilaronga and Poulsen 2020 ; Moyle et al 2013 ). IVAs can also provide services on demand such as finding entertainment for users without the need for compensation or reciprocation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Two lines of thoughts best synthetize the issues concerning sexbots. Some arguments in favour of the 'fostering sociality' hypothesis claim that sexbots will help to reduce social and emotional isolation [34], to treat relationship difficulties and erectile dysfunction, and to encourage withdrawn or differently able people to experience intimacy and sexuality, which may otherwise remain remote and unfulfilled needs for them [5]. Studies [35][36][37] suggest that individuals who have some impediments against having a fulfilled sexual life could benefit from sexbots.…”
Section: The Controversial Scientific "Sexbots" Debatementioning
confidence: 99%
“…Sexbots are relational artifacts [4] with whom people tend to form emotional bonds [2], and see them as having 'states of mind', so that an understanding of those states enriches human encounters with them. While sexbots have entered the personal lives of people, invaded their psychological imagination, and been involved in professional activities such as rehabilitation, sex care services, and selecting company staff, the meaning of a sexbot is, to a certain extent, still controversial [5,6]. Some controversy surrounds the emotional reactions that sexbots arouse.…”
Section: Introductionmentioning
confidence: 99%